Pengaruh Pendidikan Kesehatan dengan Media Telegram terhadap Efikasi Diri dalam Mengkonsumsi Tablet Tambah Darah pada Remaja Putri - Suputri, Ni Kade; Hartati, Ni Nyoman; Suratiah, Suratiah; Surinati, I Dewa Ayu Ketut; Runiari, Nengah; Sipahutar, Ida Erni; Suardani, Ni Luh Ketut (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2025)
Anemia is one of the global health problems, particularly among adolescent girls, and remains a critical issue in Indonesia. Anemia in adolescent girls can cause anemia which hurts health, academic achievement, and productivity. The government has implemented the Iron Supplement Tablet (TTD) program to reduce anemia and stunting rates. However, its implementation has not been optimal due to the low compliance among adolescents in consuming TTD. One contributing factor is the low level of self-efficacy. This study aims to determine the effect of health education using the Telegram platform on self-efficacy in consuming TTD among female students at SMPN 6 Denpasar. This study employed a pre-experimental design with a one-group pretest-posttest approach. A total of 60 respondents were selected using stratified random sampling. The independent variable was health education via Telegram, while the dependent variable was self-efficacy. The instrument used was a self-efficacy questionnaire, which had been tested for validity and reliability. The intervention was delivered once via Telegram Bot for 30 minutes. Data were analyzed using the Wilcoxon Signed Ranks Test. The results showed a p-value of 0,000 (0,05), indicating a significant effect of health education via Telegram on adolescents' self-efficacy in consuming TTD. Telegram is proven to be an effective educational medium to enhance self-efficacy and improve TTD consumption compliance among adolescent girls.